The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.37689/acta-ape/2021ao00652
|View full text |Cite
|
Sign up to set email alerts
|

Empreendedorismo e suporte familiar em estudantes de enfermagem do Brasil e Chile

Abstract: Confl itos de interesse: nada a declarar. ResumoObjetivo: Associar a tendência empreendedora geral e o suporte familiar percebido entre estudantes de Enfermagem do Brasil e Chile.Métodos: Estudo transversal com dados de estudantes de cinco instituições superiores de ensino, coletados de março a setembro de 2018. Foram utilizados: formulário para avaliação sociodemográfi ca, questionário de Tendência Empreendedora Geral (TEG) e Inventário de Percepção de Suporte Familiar (IPSF). Foram ajustados modelos de regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
20

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 29 publications
0
4
0
20
Order By: Relevance
“…Dialogued class on concepts of entrepreneurship in nursing, still based on the characteristics of nurses, which are the same as entrepreneurs, that is, it goes beyond the notion of responsible for opening new businesses, but goes through intrapreneurship, social entrepreneurship or even academic entrepreneurship, with data from current research being presented ( 3 , 4 , 12 , 19 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dialogued class on concepts of entrepreneurship in nursing, still based on the characteristics of nurses, which are the same as entrepreneurs, that is, it goes beyond the notion of responsible for opening new businesses, but goes through intrapreneurship, social entrepreneurship or even academic entrepreneurship, with data from current research being presented ( 3 , 4 , 12 , 19 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Classes are interspersed with group dynamics and games, as well as individual challenges, always focused on the development of creativity. In addition to the playful nature, these activities were inserted from studies carried out among nursing students that revealed a low tendency to creativity, an item that makes up the Global Entrepreneurial Trend, corroborated by national and international research ( 12 ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse sentido, a inclusão do empreendedorismo no ensino de graduação de Enfermagem é apontada como essencial no desenvolvimento dos futuros profissionais, permitindo refletir sobre atitudes criativas e inovadoras, com autonomia e determinação, para a excelência do cuidado de enfermagem e saúde (11)(12) .…”
Section: Introductionunclassified